2019
DOI: 10.1097/pec.0000000000001904
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Physical Examination, Old and New Biomarkers, and Ultrasonography by Using Neural Networks for Pediatric Appendicitis

Abstract: Objective:The objective of this study was to evaluate physical examinations, imaging, and laboratory analyses individually and combined using innovative statistical analysis methods for the accurate diagnosis of pediatric appendicitis.Methods: Patients admitted to hospital with symptoms of abdominal pain whose pediatric appendicitis scores greater than 3 were included in the study. Clinical, radiologic, and laboratory findings and as a new biomarker calprotectin (CPT) concentrations were evaluated individually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
(83 reference statements)
0
14
0
Order By: Relevance
“…The APPY1 panel including serum CP, WBC, and CRP has a high negative predictive value and allows reducing computer tomography utilization in patients suspected of suffering from AA, which is particularly important in case of non-adults [32][33][34][35]. More recently, a research evaluated the accuracy of clinical manifestations, laboratory analyses, and imaging methods for the diagnosis of AA [36]. They found that each marker used individually does not provide satisfying power, and the classic physical examination is still the most important single tool.…”
Section: Discussionmentioning
confidence: 99%
“…The APPY1 panel including serum CP, WBC, and CRP has a high negative predictive value and allows reducing computer tomography utilization in patients suspected of suffering from AA, which is particularly important in case of non-adults [32][33][34][35]. More recently, a research evaluated the accuracy of clinical manifestations, laboratory analyses, and imaging methods for the diagnosis of AA [36]. They found that each marker used individually does not provide satisfying power, and the classic physical examination is still the most important single tool.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil count can also be used to help identify an inflamed appendix [ 4 , 8 ] although it is not given as much consideration in the literature compared to WBC count. It can also be elevated in any infective condition and usually indicates a bacterial etiology.…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted in the systematic review by Kabir et al that CRP is better for detecting complicated or late-stage appendicitis as it is a lag indicator and is less useful for early-stage appendicitis [ 10 ]. Other papers have also demonstrated that it is less useful for acute appendicitis but significant elevation is suggestive of abscess or perforation [ 4 , 8 ]. Zani et al found that a CRP cut-off value of 40 identified one-third of paediatric patients with simple appendicitis but two-thirds of complicated appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of AA can be made more accurately, especially with repeated examinations by the same person. 7,8 Paediatric surgeons are the most competent physicians to diagnose AA. However, children with abdominal pain often present to family physicians, paediatricians and hospital emergency departments.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…For this reason, the patient should be thoroughly evaluated before the operation. The diagnosis of AA can be made more accurately, especially with repeated examinations by the same person 7,8 …”
Section: What Is Already Known On This Topicmentioning
confidence: 99%